اعوان الدولة للايالة التونسية (1735-1814): الأفراد- المجموعات- شبكات العلاقات (Revue de l'Institut des Belles Lettres Arabes, 2024)
اعوان الدولة للايالة التونسية (1735-1814): الأفراد- المجموعات- شبكات العلاقات